2019
DOI: 10.21203/rs.2.17906/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic basis for salt tolerance and disease resistance of silverleaf sunflower revealed by Iso-seq and RNA-seq

Abstract: Background Silverleaf sunflower, Helianthus argophyllus , is one of the most important wild species that have been usually used for the improvement of cultivated sunflower. Although a reference genome is now available for the cultivated species, H. annuus , its effect in helping understanding the mechanisms underlying the traits of H. argophyllus is limited by the substantial genomic variance between these two species.Results In this study, we generated a high-quality reference transcriptome of H. argophyllus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Authors assembled a high quality reference transcriptome for H. argophyllus with over 50,000 genes and found that 205 of them are not present in cultivated sunflower. Transcriptomic response to salt stress revealed more than double the number of genes (3930) that were significantly regulated in root compared to leaf (1885), which is understandable considering the higher sensitivity of root, as it is more exposed to this type of stress [68]. Transcriptomic analysis can be very useful for distinguishing gene expression in drought-sensitive and drought-tolerant genotypes [69], which is of great help for the development of drought-tolerant genotypes as one of the main goals in sunflower breeding.…”
Section: Transcriptomicsmentioning
confidence: 91%
See 1 more Smart Citation
“…Authors assembled a high quality reference transcriptome for H. argophyllus with over 50,000 genes and found that 205 of them are not present in cultivated sunflower. Transcriptomic response to salt stress revealed more than double the number of genes (3930) that were significantly regulated in root compared to leaf (1885), which is understandable considering the higher sensitivity of root, as it is more exposed to this type of stress [68]. Transcriptomic analysis can be very useful for distinguishing gene expression in drought-sensitive and drought-tolerant genotypes [69], which is of great help for the development of drought-tolerant genotypes as one of the main goals in sunflower breeding.…”
Section: Transcriptomicsmentioning
confidence: 91%
“…The significance of transcriptomic study is also reflected in the fact that it can be used for comparative analysis of genome differences between cultivated crops and wild relatives, thus revealing specific genes that can be important for improvement in the breeding process. Using a long read technique (Iso-seq) as well as RNA sequencing (RNA-seq), transcriptomic basis for salt tolerance and disease resistance of wild sunflower species (Helianthus argophyllus) was studied [68]. Authors assembled a high quality reference transcriptome for H. argophyllus with over 50,000 genes and found that 205 of them are not present in cultivated sunflower.…”
Section: Transcriptomicsmentioning
confidence: 99%